Screening ofCultivable Indigenous Fungi which Responsible for Decomposing ofRice Straw - Soni, Isnaini; Niswati, Ainin; Maryati, . (UNIVERSITY OF LAMPUNG, 2012)
The experiment was conducted to screen potentials indigenous fungi for rapid decomposing of rice straw. Seven isolates ofdominant fungi were isolated from the burying rice straw on the 2.5 cm soil depth after 30 days incubation on the paddy fields. Five dominant isolates were tested for their potential to decompose rice straw by assessing their value decreasing C/N ratio and dry weight ofrice straw. Fungal inoculums treatments were arranged in a Completely Randomized Design with four replications. The results showed that the dominant cultivable fungi thatisolated from decomposed rice straw were Trichoderma sp., Fusarium sp., Mucor sp., Aspergillus sp., and Penicillium sp. Among the tested fungi, Trichoderma sp. had the biggest ability to decompose rice straw compared to others indigenous fungi. The C/N ratio was reduced to 39.47 from an initial value of73.33 ofcontrol treatment in 10 days ofbiodegradation process in laboratory scale, thus showing the potential of indigenous Trichoderma sp. for use in large-scale composting ofrice straw.